The Effect of Personal Protective Equipment Uptake on the Risk of Leprosy in Adults: Meta Analysis - Rizki Kurniawan Saputra; Setyo Sri Rahardjo; Bhisma Murti (Journal of Health Promotion and Behavior, 2021)
Background: Leptospirosis is an acute infectious disease that can attack humans and animals caused by the Leptospira bacteria. Leptospirosis contributes to morbidity and mortality in the high-risk group, namely adults. Compliance with the use of personal protective equipment and direct contact with animal tissue infected with Leptospira sp. bacteria increase the risk of leptospirosis. This study aims to analyze the magnitude of the effect of using personal protective equipment on the risk of leptospirosis with a meta-analysis.Subjects and Method: This was a systematic review and meta-analysis carried out by following the PRISMA flow diagram. The process of searching for articles is through a journal database which includes: PubMed, Springer Link, Google Scholar and Science Direct by selecting articles published in 1999-2020. Keywords used "Leptospirosis AND Personal Protective Equipment", "leptospirosis" AND "risk factors", "leptospirosis AND adjusted odds ratio", "leptospirosis" AND "adults", "leptospirosis AND risk factors AND adjusted odds ratio". The inclusion criteria were full paper articles with observational study design, articles in English and Indonesian, multivariate analysis used with adjusted odds ratio. Articles that meet the requirements are analyzed using the Revmen 5.3 application.Results: A total of 8 articles were reviewed in this study with a cross-sectional and case-control study design. Meta-analysis of 4 case-control studies showed that non-adherence to the use of personal protective equipment had a 2.77 times increased risk of leptospirosis compared with using personal protective equipment (aOR= 2.77, 95% CI= 1.76 to 4.36, p <0.001). A meta-analysis of 4 cross-sectional studies concluded that non-adherence to the use of personal protective equipment had a 2.73 times increased risk of leptospirosis compared with using personal protective equipment (aOR= 2.73, 95% CI= 1.99 to 3.74; p= <0.001).Conclusion: Non-compliance with the use of personal protective equipment increases the risk of leptospirosis.Keywords: leptospirosis, personal protective equipment, meta-analysisCorrespondence: Rizki Kurniawan Saputra. Masters Program in Public Health, Universitas Sebelas Maret. Jl.Ir. Sutami 36A, Surakarta 57126, Central Java. Email: rizkikurniawansaputra@gmail.com. Mobile: 087738152955.Journal of Health Promotion and Behavior (2021), 06(01): 21-3https://doi.org/10.26911/thejhpb.2021.06.01.03